2015
DOI: 10.4236/ajibm.2015.54019
|View full text |Cite
|
Sign up to set email alerts
|

Towards Effective Infrastructure Development in Nigeria: Theoretical Considerations from a Project Management Perspective

Abstract: A link exists between the level of investment in infrastructure and economic growth. However, it has been shown that in spite of huge amounts earmarked for infrastructural projects, the desired outcome/benefits are not attained in many cases. This has been attributed to poor adherence to project management principles in the conception, design, and execution of these projects. This paper highlights poor project conception and definition, poor budget and stakeholder management, as well as inadequate monitoring a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 10 publications
4
8
0
Order By: Relevance
“…Many believe that the government has not displayed enough seriousness concerning infrastructure development across all sectors. Findings agree with Diugwu et al (2015), Babatunde and Perera (2017), Okolo et al (2018) and Adamu et al (2020). In summary, the authors agree that level of infrastructure development posed a great danger to accomplishing sustained growth in Nigeria.…”
Section: Findings and Discussion From The Study's Interviewssupporting
confidence: 90%
See 1 more Smart Citation
“…Many believe that the government has not displayed enough seriousness concerning infrastructure development across all sectors. Findings agree with Diugwu et al (2015), Babatunde and Perera (2017), Okolo et al (2018) and Adamu et al (2020). In summary, the authors agree that level of infrastructure development posed a great danger to accomplishing sustained growth in Nigeria.…”
Section: Findings and Discussion From The Study's Interviewssupporting
confidence: 90%
“…It was found that an increase in public sector corruption leads to a rise in the share of the public budget allocated to infrastructure procurement. Diugwu et al (2015) identified poor project conception and definition, poor budget and stakeholder management and inadequate monitoring and evaluation as major causes of Nigeria's infrastructure development failures. The United Nations Development Programme (UNDP) (2010) affirmed that procurement capability could be perceived as being three-pronged: environmental/national, company and individual.…”
Section: Procurement Management In Constructionmentioning
confidence: 99%
“…As the research [3] that a competent project manager would go a long way in addressing the problems associated with delivery of public sector funded infrastructure projects. From Percut Sei Tuan District, making roads with pavin block had been done well.…”
Section: The Effectiveness Of Village Funds In Infrastructure Arrangementioning
confidence: 99%
“…This is the best base line to create synergy in public policy. [3] good project conception and definition, proper cost and budget management, adequate stakeholder management, and the appointment of a competent project manager would go a long way in addressing the problems associated with delivery of public sector funded infrastructural projects in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…In view of this, from the connotation of health human capital, this paper discusses the impact of health human capital on economic development. 2 OLG model, also known as diamond model, is an important model to establish micro basis in macro research. Based on the OLG model, this study constructs a correlation analysis model between health human capital and economic growth based on OLG framework, and studies the correlation mechanism between health human capital and economic growth from the perspective of intertemporal consumption of individuals and enterprises.…”
Section: Introductionmentioning
confidence: 99%